ASSOCIATION BETWEEN TESTOSTERONE SUPPLEMENTATION THERAPY AND THROMBOTIC EVENTS IN ELDERLY MEN - Ramasamy, Ranjith (Urology, 2015)
OBJECTIVE: To determine the prevalence of thrombotic events and all-cause mortality in men older than 65 years with hypogonadism treated with testosterone therapy (TST). METHODS: We retrospectively reviewed the charts of 217 hypogonadal men >65 years. We compared men who received TST (n=153) to hypogonadal men (n=64) who did not receive TST. We evaluated all-cause mortality, prevalence of myocardial infarction (MI), transient ischemic attack (TIA), cerebrovascular accident (CVA, or ‘stroke’), and deep vein thrombosis / pulmonary embolism (DVT/PE). All events were verified by contacting patients. We excluded men with previous thrombotic events, men previously on androgen deprivation therapy and men who had used TST prior to age of 65. RESULTS: Median age and Charlson Comorbidity Index of men on TST (74y; 5.1) was similar between hypogonadal men not on TST (73y, p=0.48; 5.3, p=0.36). Median follow-up was 3.8 vs. 3.5 years (TST vs. no TST). No man on TST died, whereas 5 hypogonadal men who did not receive TST died (p=0.007). There were 4 thrombotic events (1 MI, 2 CVA/TIA, 1 PE) in men who received TST and 1 event (CVA/TIA) among men who did not receive TST (p = 0.8). All events (1 death, 6 months follow-up) occurred at least after 2 years of follow-up. CONCLUSIONS: There was increased all-cause mortality in hypogonadal men not treated with testosterone compared to men who received testosterone therapy. There was no difference in prevalence of MI, TIA/CVA, or PE between patients treated with testosterone and hypogonadal men not treated with testosterone.